Comparison of tende r evaluation of practice general rules against cut off for government projects - Ahmad Safwan Mohamed Yusoff (School of Environmental Engineering, University Malaysia Perlis, 2016)
The tender evaluation process for government project are using conventional method or general rules before the cut off method have been announced and implemented by Public Works Department (JKR) Malaysia in 2004. The implementation of this new statistic method was a great action in resulting the fairest condition for determining the reasonable tender price. Until now, related party of Universiti Malaysia Perlis (UniMAP) still practicing the conventional method despite of the cut off method had been introduced because of it still new, lack of knowledge about its method and high difficulty expectation rather than conventional method. The objectives of this research are; (1) to analyze the tender evaluation process based on the latest Ministry of Financial (MOF) 2008 edition guideline; (2) to find out cut-off method system and where it is occur and the last one is; (3) to analyze the project data collected using both method which are conventional and cut off method and state the comparison between conventional and cut off method which will bring us to know advantages and disadvantages for both of them as it enable us to determine the best method in tender evaluation usage. There are two construction project will be use as a case study to analyze the cut-off price calculation package during cut-off method usage. This research at least would show clearly the best method either conventional or cut off method which can be practiced especially by Universiti Malaysia Perlis (UniMAP) and generally for other government development unit.